ECONOMIC SITUATION OF THE BESSARABIAN GOVERNORATE NOBLES DURING THE FIRST WORLD WAR - Zakharova, Oksana (International Journal of Innovative Technologies in Social Science, 2020)
After the annexation of Bessarabia to the Russian Empire, a noble class of the representatives of local elite was formed on its territory. Due to the deteriorating economic situation of the upper class of the Bessarabian governorate during the First World War, only 590 people participated in the political and economic life of the governorate and the country. The reason for this was the decrease in the number of land ownership among the nobility of the governorate. In the early twentieth century, the land plots that belonged to the landlords were the symbol of prosperity for them, and they gave the opportunity to the hereditary nobles to participate in the deputy nobility meetings and the election of members of the town council to the County Zemstvo Assembly. During the First World War the Bessarabian governorate nobles played a social role not only of the landlords, officials and the army men, but also teachers, doctors and engineers. Therefore, their incomes were different, in accordance with the established salaries. The purpose of the article is to study the economic condition of the Bessarabian governorate nobles, depending on their activities. Using a comparative method, it became known that the share of nobles land ownership in the Bessarabian governorate during the First World War was declining, which led to the mastering of new professions for the nobility of the Russian Empire. The most affluent were high-ranking officials, such as ministers and deputies of the State Duma, as well as the governor and senior officers. The least well-off in terms of income were the landlords with land ownership of up to 100 acres, representatives of the professions inherent in the intellectuals.